An atypical presentation of hypothyroidism with extremely exaggerated functional impairment - Alireza Arezoumand; Sahar Nazari; Kimia Jazi; Mohammad Bagherzade; Mohammad Mehdi Riahi; Melika AkbariMehr; Narges Kanganee; Maryam Masoumi (Clinical Case Reports, 2023)
Key Clinical Message Myopathy‐related symptoms are rare manifestations of hypothyroidism. Clinicians should consider hypothyroid myopathy as one of the possible diagnoses for patients with proximal weaknesses. Abstract Myopathy‐related symptoms are rare manifestations of hypothyroidism. Clinicians should consider hypothyroid myopathy as one of the possible diagnoses for patients with proximal weaknesses. We report a 34‐year‐old woman, presenting with a new atypical musculoskeletal manifestation of hypothyroidism mimicking polymyositis.